Analysis of Sr2Mg (BO3)2Tb3+ Green Emitting Phosphor for Solid State Lighting: Implication for Light Emitting Diode (LED) - Panse, Vishal R; Rahate, Gaurav; Saregar, Antomi; Kaur, Manmeet; Dixit, Aparna (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
With the assist of customized step wise combustion synthesis method Sr2Mg(BO3)2: Tb3+ phosphors were synthesize along with the luminescent proprieties, XRD, chromaticity coordinates with effect of emission intensity with related with the corresponding concentration were studied. The emission spectrum of Sr2Mg(BO3)2 :Tb3+ (x=0.2 to 2 mol percent) excited by 353 nm exhibits a strong green emission among peak location at 546 nm is recognized to F-F transitions of Tb3+ 5D4-7F5 ion. This study suggest that Sr2Mg(BO3)2: Tb3+ phosphor be a prominent material as a green constituent for phosphor- transformed W-LEDs for SSL